Challenges and management of venomous bites and scorpion stings in Lebanon: a qualitative study - Kadi, Kamil; El-Zahran, Tharwat; Badr, Mario; Mdaihly, Mohammad; Ahmad, Nesrine; Berri, Atika; Bauer, Michelle E. E.; Al-Hajj, Samar (Frontiers in Public Health, 2025)
BackgroundSnakebites and scorpion stings are significant public health issues globally, particularly in the Middle East. This qualitative study investigates the management of these incidents in Lebanon by exploring the perceptions of healthcare providers and public health experts.MethodsThematic analysis, guided by sociocultural theory, examined qualitative data from 17 interviews with healthcare providers, including emergency physicians, paramedics, pharmaceutical providers, and ministry workers. Transcripts were coded to identify recurring themes related to the management of snakebites and scorpion stings, focusing on availability, accessibility, inequity, healthcare access disparities, and cultural influences on treatment-seeking behavior.ResultsThe analysis revealed significant disparities in antivenom availability and accessibility, particularly in rural areas and among low socioeconomic groups. Healthcare providers often resorted to illicit channels to secure antivenom due to stock shortages, while victims sometimes relied on traditional treatment methods. The lack of standardized treatment protocols and inadequate clinician training resulted in inconsistent antivenom usage and unsafe practices. The study also highlighted insufficient documentation and reporting mechanisms and inadequate networking among stakeholders, alongside a notable knowledge gap among victims.ConclusionThis study emphasizes the urgent need for targeted interventions to address systemic challenges in managing snakebites and scorpion stings in Lebanon. Collaborative efforts are essential to enhance awareness, improve antivenom access, standardize treatment protocols, and promote effective management practices.